2022
DOI: 10.1161/hypertensionaha.121.17979
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Left Ventricle Mitochondrial Dysfunction After Neonatal Exposure to Hyperoxia: Relevance for Cardiomyopathy After Preterm Birth

Abstract: Background: Individuals born preterm present left ventricle changes and increased risk of cardiac diseases and heart failure. The pathophysiology of heart disease after preterm birth is incompletely understood. Mitochondria dysfunction is a hallmark of cardiomyopathy resulting in heart failure. We hypothesized that neonatal hyperoxia in rats, a recognized model simulating preterm birth conditions and resulting in oxygen-induced cardiomyopathy, induce left ventricle mitochondrial changes in juvenile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 63 publications
(117 reference statements)
0
7
0
Order By: Relevance
“…The consistent underlying mechanism behind these protective effects involves the modulation of oxidative stress. For instance, a study utilizing a rat model of preterm birth demonstrated significant alterations in the structure and function of the cardiac left ventricle mitochondria following transient neonatal exposure to hyperoxia [ 29 ]. These alterations encompassed a reduction in mitochondrial size and integrity, along with a subsequent decline in oxidative phosphorylation capacity later in life.…”
Section: Discussionmentioning
confidence: 99%
“…The consistent underlying mechanism behind these protective effects involves the modulation of oxidative stress. For instance, a study utilizing a rat model of preterm birth demonstrated significant alterations in the structure and function of the cardiac left ventricle mitochondria following transient neonatal exposure to hyperoxia [ 29 ]. These alterations encompassed a reduction in mitochondrial size and integrity, along with a subsequent decline in oxidative phosphorylation capacity later in life.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore possible that these long-term effects of cysteine deficiency-and to a lesser extent, vitamin C deficiency-in the neonatal period could increase the risk of pulmonary conditions such asthma and chronic obstructive pulmonary disease. Indeed, preterm neonates that go through neonatal oxidative stress often develop these conditions at adulthood [1][2][3][4][5][6][7][8][9][10][11]. Future studies should focus on the effect of these neonatal deficiencies on the development of chronic lung diseases in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Very premature birth (≤32 weeks of gestation) is associated with several short-and long-term consequences over the development of several diseases. In neonatal life, infants born prematurely develop complications such as bronchopulmonary dysplasia [1], and they are at higher risk of developing asthma, chronic obstructive pulmonary disease (COPD) and other respiratory complications in adulthood [2,3], as well as other complications [1,2,[4][5][6][7][8][9][10][11]. Despite the strong clinical evidence, it is challenging to seize what specific aspects of prematurity lead to the increased risk of neonatal and adult diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperoxia can also induce cardiac injury. Rats exposed to hyperoxia exhibit decreased oxidative phosphorylation and increased markers of glycolysis in the muscle tissue of the left ventricle [ 85 ]. Cohen et al found that hyperoxia reduced fatty acid synthesis in atrial cardiomyocytes, leading to inhibited cell proliferation and survival [ 86 ].…”
Section: Metabolic Reprogramming In Neonatal Hyperoxia-associated Dis...mentioning
confidence: 99%